Generalized Impairment of CD8+ T-cells in HCV Mono- and HIV-HCV Co-infection - Burke, Stephanie (Université d'Ottawa / University of Ottawa, 2015)
Chronic hepatitis C virus (HCV) infection has global effects on the immune system. CD8+ T-cells, responsible for viral clearance and control, are dysfunctional for as yet unknown reasons. It is hypothesized that IL-7 signaling pathway deficiencies contribute to this impairment. Blood-derived CD8+ T-cells in chronic HCV mono- and HIV-HCV co-infection had lower IL-7-induced activation of STAT5 and production of Bcl-2, and lower proliferation in co-infection, compared to controls. Lower Bcl-2 production was also associated with increased fibrosis. These changes were independent of the IL-7 receptor α expression and suppressor of cytokine signaling 1 or 3 expression. Intrahepatic CD8+ T-cells in HCV-infection did not activate STAT5 above basal levels with cytokine stimulation and had lower Bcl-2 expression than blood-derived cells. In conclusion, bulk CD8+ T-cells were impaired in response to IL-7 and the IL-7 signaling pathway may be one mechanism by which CD8+ T-cells are impaired in chronic HCV infection.
Keywords: Hepatitis C Virus; CD8+ T cell; HIV